A Sufi-Jewish Dialogue : Philosophy and Mysticism in Bahya ibn Paquda's "Duties of the Heart" - Lobel, Diana (Book collections on Project MUSE., 2007)
In A Sufi-Jewish Dialogue, Diana Lobel explores the full extent to which Duties of the Heart marks the flowering of the "Jewish-Arab symbiosis," the interpenetration of Islamic and Jewish civilizations.